IMPROVING ENGLISH SPEAKING SKILLS OF STUDENTS OF SDN 094136 THROUGH CLASSROOM ACTIVITIES - Ahmad Amin Dalimunte; Nurul Husna; Sabilla Ayu Andini; Cindy Alia Ramadhany (Argopuro: Jurnal Multidisiplin Ilmu Bahasa, 2024)
This study aims to improve students' English-speaking skills at SD Negeri 094136, Sait Buttu Village, by implementing innovative classroom activities such as role-play, group discussion, language games, and presentation. These activities were designed to address the challenge of low English skills due to lack of facilities, qualified teaching staff and exposure to English in the students' environment. This study used a pretest-posttest design with qualitative and quantitative approaches to evaluate the effectiveness of the methods. The respondents were students in grades 2, 3, and 4. The results showed a significant improvement in students' speaking fluency, pronunciation accuracy, and vocabulary acquisition. In addition, there was an increase in students' self-confidence although the challenge of speaking anxiety was still present. The study concluded that communicative and interactive classroom activities were effective in improving students' speaking skills. Research recommendations include the integration of speaking activities in the educational curriculum and the need for further research in various contexts to explore the effectiveness of this method more widely.